Immunization in traveler's health (Portuguese Journal of Family Medicine and General Practice, 2003)
There are two main reasons to vaccinate travelers: protection for the individual to avoid contracting diseases in the country of destination and for the protection of the vulnerable population of the country of origin for imports of diseases in the return trip.